2005
DOI: 10.1118/1.2107047
|View full text |Cite
|
Sign up to set email alerts
|

Optimized interstitial PDT prostate treatment planning with the Cimmino feasibility algorithm

Abstract: The primary aim of this study was to determine whether optimized photodynamic therapy (PDT) treatment planning (seeking optimized positions, lengths, and strengths of the light sources to satisfy a given dose prescription) can improve dose coverage to the prostate and the sparing of critical organs relative to what can be achieved by the standard PDT plan. The Cimmino algorithm and search procedures based on that algorithm were tested for this purpose. A phase I motexafin lutetium (MLu)-mediated photodynamic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 41 publications
0
75
1
Order By: Relevance
“…Other groups have previously proposed using the Cimmino feasibility algorithm (Censor et al 1988) to optimize the diffuser outputs (Altschuler et al 2005, Johansson et al 2007. However, De Pierro and Iusem (1985) have shown that, for the inconsistent case, the Cimmino algorithm minimizes (2.8) rather than (2.5), making the comparison of different diffuser positions in the outer loops inconsistent.…”
Section: Inner Loop-mentioning
confidence: 99%
See 3 more Smart Citations
“…Other groups have previously proposed using the Cimmino feasibility algorithm (Censor et al 1988) to optimize the diffuser outputs (Altschuler et al 2005, Johansson et al 2007. However, De Pierro and Iusem (1985) have shown that, for the inconsistent case, the Cimmino algorithm minimizes (2.8) rather than (2.5), making the comparison of different diffuser positions in the outer loops inconsistent.…”
Section: Inner Loop-mentioning
confidence: 99%
“…The cost function (2.5) expresses the weighted sum of all square deviations from the prescribed dose range, and it is similar to equation (4) in (Altschuler et al 2005):…”
Section: Solution To the Inverse Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…98 A kernelbased algorithm was developed to calculate light fluence rate distribution in the optically heterogeneous prostate gland, 109 which, coupled with an optimization engine allows optimization of light source powers to achieve a uniform light fluence distribution. 110,98 This area of research will evolve into a totally computerized delivery, monitoring, and dosimetry system for real-time feedback control.…”
Section: Ivd Treatment Planning Integrated With Dosimetry Imagingmentioning
confidence: 99%